Translation and Validation of the Indonesian Version of Oral Chemotherapy Adherence Scale (OCAS) - Puspitasari, Atika Wahyu; Kristina, Susi Ari; Satibi, Satibi; Prabandari, Yayi Suryo (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: Medication adherence is essential for oral anticancer agents (OAAs) to succeed and maintain the optimal therapeutic outcomes. However, there are no well-established instruments in Indonesia to evaluate adherence to oral chemotherapy by cancer patients.Objectives: This study aimed to validate and translate the Oral Chemotherapy Adherence Scale (OCAS) for cancer patients in Indonesia.Methods: Data were collected from patients taking oral chemotherapy for at least a month at Dharmais Cancer Hospital in Jakarta. OCAS was translated into Indonesian using a forward-backward translation method. Content validity was assessed through expert review to calculate Content Validity Index (CVI), while face validity was evaluated to confirm cultural relevance and readability. Internal consistency was measured using Cronbach's alpha.Results: A total of 131 patients participated from August to December 2021. Content validation by seven experts showed that the mean I-CVI of the items was above 0.79, with an S-CVI of 0.985, reflecting the validity of the items. Furthermore, face validity confirmed the readability and clarity of Indonesian version of OCAS. Reliability testing showed a Cronbach alpha of 0.871, suggesting strong internal consistency.Conclusion: Indonesian OCAS was a valid instrument for evaluating medication adherence in Indonesian cancer patients taking oral chemotherapy. Therefore, it can be used for adherence monitoring in healthcare settings.